2012
DOI: 10.2105/ajph.2011.300348
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Incentives, Equity, and the 5 Groups Problem

Abstract: Wellness incentives are an increasingly popular means of encouraging participation in prevention programs, but they may not benefit all groups equally. To assist those planning, conducting, and evaluating incentive programs, I describe the impact of incentives on 5 groups: the “lucky ones,” the “yes-I-can” group, the “I'll-do-it-tomorrow” group, the “unlucky ones,” and the “leave-me-alone” group. The 5 groups problem concerns the question of when disparities in the capacity to use incentive programs constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 9 publications
1
18
0
4
Order By: Relevance
“…The typologies of women reported by Nichter and colleagues 110 and Radley and colleagues 113 for smoking cessation incentive programmes in pregnancy, and the typology for a wider range of wellness incentives described by Schmidt,271 resonate with our data and influence engagement and behaviour outcomes. These typologies have important implications for policy decisions about whether incentives are universal, the preferred option in our study, or targeted to those who have the capacity to benefit and/or who are most likely to succeed.…”
Section: Fit With the Literaturesupporting
confidence: 80%
See 1 more Smart Citation
“…The typologies of women reported by Nichter and colleagues 110 and Radley and colleagues 113 for smoking cessation incentive programmes in pregnancy, and the typology for a wider range of wellness incentives described by Schmidt,271 resonate with our data and influence engagement and behaviour outcomes. These typologies have important implications for policy decisions about whether incentives are universal, the preferred option in our study, or targeted to those who have the capacity to benefit and/or who are most likely to succeed.…”
Section: Fit With the Literaturesupporting
confidence: 80%
“…Indeed, typologies of the impact of incentives on five groups of individuals -the 'lucky ones', the 'yes I can' group, the 'I'll do it tomorrow' group, the 'unlucky ones' and the 'leave me alone' group -have implications for whether incentives should be universal, targeted or abandoned. 271 Unintended consequences are reported in some studies, with gaming to receive the incentive seeming more likely if the incentive rewards attendance rather than the actual desired behaviour. Incentive studies for complex lifestyle behaviours are therefore predominantly hypothesis generating and have largely targeted individuals and further research into targeting other populations is indicated, for example families, communities and workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Where incentives have this effect, it is a clearcut case of long term harm. When the benefits are substantial, the disparities may become even more inequitable31; the health status of groups that are at the lower end of the social ladder might be at risk of moving even farther from groups at the higher end. Patterns of systematic disadvantage may become further entrenched as a result.…”
Section: What Are the Potential Long Term Harms Of Health Incentive Imentioning
confidence: 99%
“…Another large employer in the financial industry rewarded employees for meeting personalized goals, such as exercising four times a week or increasing fruit and vegetable intake. Such progress-oriented incentives may be particularly useful for motivating individuals with complex conditions or a number of health risk factors, as small steps may be perceived attainable (6).…”
Section: Health Policy and Managementmentioning
confidence: 99%